Addressing mental health challenges among medical students: A narrative review - Mohd Noor, Hanisah; Che Mat, Khairi; Hanizam, Halimah; Tengku Kamarulbahri, Tengku Mohd Saifuddin (Journal of Islamic, Social, Economics and Development, 2025)
Medical students are disproportionately affected by psychological distress, including higher rates of anxiety, depression, and burnout, compared to their non-medical peers. This review critically examines the mental health challenges among medical students, highlighting the compounded effects of academic and clinical stressors. Evidence-based interventions, such as Cognitive Behavioral Therapy (CBT) and mindfulness programs, are analyzed for their effectiveness in mitigating mental health issues. This review also includes a case study demonstrating the application of CBT in managing depressive symptoms and enhancing self-esteem in a medical student. The findings advocate for a comprehensive, multifaceted approach to mental health in medical education, emphasizing early identification, preventive strategies, and targeted therapeutic interventions. Such an approach is crucial for ensuring the well-being of medical students, ultimately contributing to better patient care and more resilient healthcare professionals.